THE INFLUENCE OF PSYCHOLOGICAL COST, RELIGIOSITY, LOVE OF MONEY, EDUCATION LEVEL AND TAX SOCIALIZATION ON INDIVIDUAL TAXPAYER COMPLIANCE - Tiara Aulia Elsa Pradina; Anggoro, Rusmawan Wahyu (LPPM STIE YKPN Yogyakarta, 2024)
This study aims to determine the influence of psychological costs, religiosity, love of money, education level and tax socialization on the compliance of individual taxpayers. The data collection of this research uses an e-questionnaire (google form). Hypothesis testing uses multiple linear regression analysis. The SPSS program is used to process and test research data. The results of the study show that religiosity, tax socialization, and education level have a significant effect on the compliance of individual taxpayers. This study was unable to find evidence that supports the influence of psychological costs, love of money. Tax socialization has the highest influence on taxpayer compliance, followed by religiosity and education level. The dominance of respondents among employees who receive income tafter taxes deduction as one of the limitations of this article.